2008
DOI: 10.1021/la8012014
|View full text |Cite
|
Sign up to set email alerts
|

Poly(d,l-lactide-co-glycolide) Nanoparticle Agglomerates as Carriers in Dry Powder Aerosol Formulation of Proteins

Abstract: A dry powder aerosol drug delivery system was designed with both nano- and microstructure to maximize the protein loading via surface adsorption and to facilitate delivery to the deep lung, respectively. Ovalbumin was employed as a model protein to adsorb to and controllably flocculate DOTAP-coated PLG nanoparticles into “nanoclusters” possessing low density microstructure. The mechanism of nanoparticle flocculation was probed by evaluating the effects of ionic strength, shear force, and protein concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Positively-and negatively charged biodegradable nanoparticles are brought into contact under vigorous stirring, and spontaneous composite microparticle formation takes place. Nanoparticle aggregation is driven by electrostatic attraction/forces in this case [129,130].…”
Section: Polymeric Nanoparticles As Inhalative Drug-delivery Vehiclesmentioning
confidence: 99%
“…Positively-and negatively charged biodegradable nanoparticles are brought into contact under vigorous stirring, and spontaneous composite microparticle formation takes place. Nanoparticle aggregation is driven by electrostatic attraction/forces in this case [129,130].…”
Section: Polymeric Nanoparticles As Inhalative Drug-delivery Vehiclesmentioning
confidence: 99%
“…Despite the fact that particles less than 1 μm have challenging delivery limitations, nanoparticles have attracted considerable interest in the dry powder inhalation application [13,73,140,[165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182]. Nanoparticles fall in the same size range of different cell organs like ribosomes, cell receptor, transporter, etc.…”
Section: Nanoparticle Formulationmentioning
confidence: 99%
“…It is reported that small nanoparticles have slower clearance than large nanoparticles in the size range of 20-200 nm [203]. rifampicin with PLGA (poly (lactic-coglycolide)) [165], chitosan with lactose and mannitol [176,181], insulin [170], ovalbumin [169], doxorubicin [178] etc. Though nanoparticles pose several health risks such as toxicity and instability [205,206], it provides immense promise in aerosol therapeutics field.…”
Section: Nanoparticle Formulationmentioning
confidence: 99%
“…27 Additionally, high FPFs are achieved with the hollow, porous particles when delivered as a pMDI, ranging from 40% to 70% for a wide variety of drugs. 17,[27][28][29] Particles with a similar morphology to hollow, porous particles include large porous particles (LPP) 4,18 and large porous nanoparticle (LPNP) aggregates, [30][31][32][33][34] which are produced by spray drying and have sizes ranging from 10 to 20 mm. These powders exhibit FPFs as high as 60% when administered as a dry powder due to their low density (<0.4 g/ cm 3 ).…”
Section: Introductionmentioning
confidence: 99%